ADOPTION OF MOBILE-BASED INFORMATION SYSTEM AMONG SUGARCANE FARMERS IN INDIA - Kumar, Ritik; Tomar, Anuj; Sharma, Anu; Negi, Rakesh Singh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Across the global South, smallholder farmers face problems accessing information that limits their ability to participate fully in rural development. Mobile-based information systems can act as a catalyst for the digital inclusion of farmers and can improve their social, economic, and informational capacities. The study applied the Socio-technical system theory to analyse the adoption of information systems among farmers for their digital inclusion. The study adopted a descriptive research design, and the multi-stage purposive sampling was used for collecting data from 320 smallholder farmers in the region. Result highlights that the socio-economic characteristics of farmers are corelated with the adoption of information systems among farmers. In addition, they face challenges such as affordability, digital literacy and trust in adopting the information system. Finally, the findings of study have significant implications for researchers studying the relationship between society and technology and for policymakers designing digital policies related to the digital inclusion of rural communities.